Defensive expenditures: the hidden face of blackberry competitiveness in Michoacán, Mexico - Ortiz-Paniagua, Dr. Carlos F.; Cervantes-González, Carlos Timoteo (Ecosistemas y Recursos Agropecuarios, 2025)
Michoacan is a significant producer of blackberries, but there are concerns about the health implications for day laborers and their families due to agrochemical exposure. This study aims to calculate the hidden health-related costs incurred due to agrochemical use, which are often overlooked by businesses. The study was conducted in Los Reyes, Michoacan, Mexico, and utilized contingent valuation and means testing to estimate these defensive health expenses, which amount to approximately USD 126 012. The findings suggest that compensatory measures could be put in place, and the study identifies variables such as frequency of illness, exposure to agrochemicals, income, and number of children as critical factors. This research offers insights into the external costs associated with agrochemical use and proposes measures to address these issues.
Keywords: Defensive expenditures; economic compensation; externalities; environmental economics